(untitled) (Хабаршы. Психология және социология сериясы, 2023)
Distance learning has been implemented since the COVID-19 pandemic worldwide, including in Indonesia. The results of previous studies said that teachers were overwhelmed in carrying out their duties, the effect on work stress. This research was conducted on 98 teachers who ran online learning during the COVID-19 pandemic—collecting data using a work stress scale and an open-ended question-naire. The results showed that the teacher’s job stress was in the medium category. There are more male teachers in the high category than female teachers. Teacher problems are divided into three categories: problems with teachers, students, and technical support, triggering many impacts. The principal’s role in overcoming the problems that arise is considered quite active, although some say that the principal is less concerned. Based on the results of this study, it can be concluded that teachers experience work stress in the medium and high categories during online learning during the COVID-19 pandemic. Problems faced by teachers include problems originating from teachers such as the difficulty of time management, difficulty in evaluating learning outcomes, and feeling less than optimal in educating students, originating from students such as students ignoring assignments, not following Online class, students not being active. Key words: work stress, distance learning, online learning, teacher stress, principal role, work from home, pandemic COVID-19.